Evaluation of Measures of Association on Dental Anxiety Management (Journal of Pharmaceutical Negative Results, 2023)
Background Dental anxiety is an issue faced by children globally, which denies access to the right treatment modalities.KAP studies include three components namely knowledge, attitude and practice. They assess health care delivery systems. The present study aimed to compare the effectiveness between an audio-visual educational module over a traditional instruction module in improving assistance to combat dental anxiety. Materials and Methods Sixteen patients were recruited in each group for the study and followed up for a six month period in Chennai city. The knowledge, attitude and practice of parents regarding dental anxiety management strategies were assessed by way of an empirical inquiry guide. Results There was a significant improvement in the knowledge aspect of anxiety management from baseline to 6 months, with audio visual aid showing a better response in comparison with the traditional module. Conclusion Customized audio visual aid served the purpose of reducing dental anxiety by a great extent in comparison with the traditional module. This was readily accepted by the parents of the children who participated in the study.